Language Learning Strategies and Academic Success: A Mexican perspective - Del Ángel Castillo, Martha Catalina; Tecnológico de Monterrey Campus Monterrey (2013)
The authors´ goal is to explore the language learning strategies most frequently used by academically successful students in higher education. As language learning strategies is a field that needs to be deeply explored, Mixed Method Design was selected. This study was performed in three phases: (i) quantitative: it describes the results after analyzing a population of 1283 students who answered a general questionnaire and The Strategy Inventory for Language Learning (Oxford, 1990). (ii) qualitative: it describes how a sample was selected as a result of phase I and how the interviews were held. (iii) interpretation: it combines the previous stages. The results revealed that language learning strategies along with other personal and family complements lead students to reach academic success.